2021
DOI: 10.1016/j.ccell.2021.04.001
|View full text |Cite
|
Sign up to set email alerts
|

STAG2 mutations alter CTCF-anchored loop extrusion, reduce cis-regulatory interactions and EWSR1-FLI1 activity in Ewing sarcoma

Abstract: Highlights d STAG2 promotes anchored chromatin extrusion at CTCF loop boundaries d STAG2 LOF reduces cis-mediated EWSR1-FLI1 transcriptional activity d STAG2 LOF increases mesenchymal features and migratory potential of Ewing cells d STAG2 LOF signature is associated with adverse prognosis in Ewing sarcoma

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 109 publications
2
58
0
Order By: Relevance
“…In epithelial cancer cells, RAD21 depletion alters chromosome interactions around TGFB1 and ITGA5, leading to their activation and epithelial to mesenchymal transition [127]. STAG2 knockout in Ewing sarcoma cell lines was found to downregulate EWSR1-FLI1-anchored chromatin interactions and enhance the migratory potential of these cells [138]. Together these studies show that cohesin insufficiency can result in diverse aberrant cellular phenotypes.…”
Section: Cohesin In Cancermentioning
confidence: 85%
“…In epithelial cancer cells, RAD21 depletion alters chromosome interactions around TGFB1 and ITGA5, leading to their activation and epithelial to mesenchymal transition [127]. STAG2 knockout in Ewing sarcoma cell lines was found to downregulate EWSR1-FLI1-anchored chromatin interactions and enhance the migratory potential of these cells [138]. Together these studies show that cohesin insufficiency can result in diverse aberrant cellular phenotypes.…”
Section: Cohesin In Cancermentioning
confidence: 85%
“…In vertebrate somatic cells, there are two types of cohesin subunit protein, SA1 and SA2 (encoded by STAG1 and STAG2 genes), which hold SMC3, SMC1, and RAD21 proteins to form the cohesin protein complex, called cohesin-STAG1 and cohesin-STAG2 [ 218 ]. STAG2 is the most frequently mutated in solid cancers [ 219 , 220 ], and in hematologic malignancies, genes including STAG1 , STAG2 , RAD21 , SMC1A , and SMC3 are frequently mutated [ 221 223 ]. Also, precocious dissociation of sisters 5 (PDS5) is an associated protein of cohesin complex [ 224 ].…”
Section: Key Structural Elements Mediating 3d Chromatin Interactionsmentioning
confidence: 99%
“…It has been suggested that STAG2 LOF increases the chance that mutated cells acquire tumor-driving mutations by extending cell life span [ 146 ]. This notion is supported by the observation that transcription factors ( MYC , NF-κB ) or signaling pathways (epithelial-to-mesenchymal transition, TGF-β , and EGF ) are impacted upon STAG2 LOF suggesting that these alterations may contribute to tumorigenesis [ 147 ].…”
Section: Effects Of Cohesin Dysfunction In Cancermentioning
confidence: 99%